2021
DOI: 10.3390/foods10020383
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol-Rich and Alcoholic Beverages and Metabolic Status in Adults Living in Sicily, Southern Italy

Abstract: Polyphenol-rich beverage consumption is not univocally accepted as a risk modulator for cardio-metabolic risk factors, despite mechanistic and epidemiological evidence suggesting otherwise. The aim of this study was to assess whether an association between polyphenol-rich beverage consumption and metabolic status could be observed in a Mediterranean cohort with relatively low intake of tea, coffee, red and white wine, beer, and fresh citrus juice. Demographic and dietary characteristics of 2044 adults living i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…However, our previous study conducted in the Polish population with cardiovascular disease showed that tea consumption was 2-fold higher than coffee [ 49 ]. Low intake of coffee was also observed in the Mediterranean population [ 54 ].…”
Section: Discussionmentioning
confidence: 94%
“…However, our previous study conducted in the Polish population with cardiovascular disease showed that tea consumption was 2-fold higher than coffee [ 49 ]. Low intake of coffee was also observed in the Mediterranean population [ 54 ].…”
Section: Discussionmentioning
confidence: 94%
“…The pathophysiology of the inverse coffee consumption-T2D association can be explained in the following ways. First, coffee is a repository of phenolic compounds rich in antioxidant activity [ 49 50 ], protective against inflammation [ 51 52 ] and neurodegenerative diseases, including T2D, in some observational studies [ 53 54 ], intervention trials [ 55 ], and reviews [ 50 56 57 ]. Second, suppressed fat accumulation due to the inhibitive potential of quinic acids from phenols on the nuclear activity of sterol regulatory element-binding protein 1c, acetyl-CoA carboxylase activity, and cellular malonyl-CoA levels were reported in C57BL/6J mice on a high-fat diet supplemented with coffee-derived phenols [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of coffee consumption was quite heterogeneous among the included studies, with most of them classifying high coffee consumption above or equal to three cups a day [26,27,29,36,41,47], and low consumption was considered non-consumption or less than once a day or week. The volume of coffee per cup was evaluated in 8 studies [27,28,31,36,38,43,44,50], ranging from 50 to 237 mL. All studies were conducted on adults.…”
Section: Characteristics Of Studies Included In the Meta-analysismentioning
confidence: 99%
“…A total of 463,973 participants (321,978 from 12 cohort studies and 141,995 from 13 crosssectional studies) were included in the meta-analysis. Overall, 11 studies were conducted in Europe [26,28,30,31,33,34,37,38,40,41,44], 9 studies in Asia [29,32,35,36,39,42,[47][48][49], and 5 studies in the United States [27,43,45,46,50]. Twenty studies did not distinguish between sexes [26][27][28][29][31][32][33][34][35][36][37][38][39][41][42][43][44][47][48][49], two studies were conducted on men only [40,46], and three studies on women only [30,…”
Section: Characteristics Of Studies Included In the Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation